Materiality of Disclosure of Non-financial Sustainability Information and Company Financial Performance: Evidence from Australian Listed Companies - Mamun, Ashraf Al (American Journal of Trade and Policy, 2021)
The broad objective of this paper is to investigate the relationships between the disclosure of non-financial material sustainability information and the financial performance of listed Australian companies in the materials sector. Using firm-level fixed-effects analysis for all companies, the findings show a mixed relationship (no relationship or statistically significant negative relationship) between lagged aggregate non-financial material sustainability disclosure and financial performance of Australian listed companies in the materials sector. The present study contributes to the existing literature on disclosure of non-financial sustainability information by adding insights into the materiality concept of non-financial sustainability disclosure in the Australian context. The evidence from the current study is expected to provide useful information for the companies’ stakeholders in Australia who use both financial and non-financial information for formulating business and regulatory policies and for decisions regarding the persistent expansion of sustainability reporting requirements. Funding Acknowledgement: This study is funded by the “Australian Government Research Training Program (RTP) Scholarship”.